The burnings - Lees, Julian (Constable, an imprint of Little, Brown Book Group, 2018)
With discovery comes certain death ... When Australian Jillian Parker's scorched remains are discovered in her burnt-out car Ruud Pujasumarta and his team are brought in to investigate what appears at first to be a routine homicide. But when Canadian citizen Anita Dalloway's charred body is found a few days later Ruud finds a banner unfurled by the corpse's feet. A verse from the Quran is scribbled across it, calling for unbelievers to be burned. The killer is targeting Christians. And the team's suspicions are confirmed when a third body, that of English backpacker Emily Grealish, turns up with the same M.O. But who is responsible? Is it the senior Australian diplomat from the embassy who was obsessed by the first victim? The Imam who preaches Sharia law? The Indonesian three-star military general taking backhanders and living a life of luxury in Jakarta? Or the local drug dealer with a score to settle? But Ruud is suspicious that the killer may be someone much closer to home, someone Ruud has trusted for many years. What unravels is a terrifying chain of events for Ruud. And what he discovers puts his and those around him lives in danger.